Voices beyond the wall : twelve love poems from the murder capital of the world - Coley, Brad; Stories Matter Media; Soundview Media Partners ([San Francisco, California] : Stories Matter Media, 2017)
Rescued from the streets of San Pedro Sula, Honduras, murder capital of the world, orphaned girls find their voices in poetry as they heal traumas of their past and prepare to transition into an uncertain future. --
Visits Our Little Roses, an orphanage for girls in San Pedro Sula, Honduras, where Spencer Reece, an Episcopal priest as well as a renowned poet, teaches poetry to the girls, guiding them as they work on a book of their own poems.
Originally released as a motion picture in 2017.
Featuring Spencer Reece.
Cinematographer, Carmen Osterlye ; editors, Elise Durant, Seth Anderson ; music, Beth Custer.
In English and Spanish; with English subtitles.
Best Documentary, St. Louis International Film Festival Interfaith Awards, 2017
Frank Little Award for Self-Sacrifice and Social Change, Covellite International Film Festival, 2017
Keywords: Our Little Roses (Orphanage : San Pedro Sula, Honduras); Reece, Spencer; Orphanages -- Honduras -- San Pedro Sula; Orphans -- Honduras -- San Pedro Sula -- Social conditions; Orphans -- Services for -- Honduras -- San Pedro Sula; Girls -- Honduras -- San Pedro Sula -- Social conditions; Homeless girls -- Services for -- Honduras -- San Pedro Sula; Poetry -- Study and teaching -- Honduras; Children's poetry, Honduran; San Pedro Sula (Honduras) -- Social conditions; Teenage girls -- Honduras -- Biography; Girls -- Honduras -- Biography; Teenage girls -- Poetry; Girls -- Poetry; Poetry; Social problem films; Nonfiction films; Documentary films; Internet videos; Streaming video